TRENDS OF PREDUCTAL AND POSTDUCTAL OXYGEN SATURATIONS IN PRETERM INFANTS IMMEDIATELY AFTER BIRTH - SHAON MITRA,; ARNAB MONDAL, (International Journal of Pharma and Bio Sciences, 2016)
Studies on healthy term newborns have shown that during transition from fetal to neonatal circulation, the oxygen saturation (SpO2) values are initially low and gradually increase to normal. The postductal SpO2 is consistently lower than the preductal SpO2 but their difference gradually decreases after birth. The present study aims to find out the trend of preductal-postductal SpO2 gradient in preterm infants.1 In preterm infants, the ductus arteriosus remains patent for longer, and due to the relatively increased pulmonary vascular resistance, the right to left shunt occurs for a longer period. Hence the preductalpostductal SpO2 gradient may persist longer. This study shows that the preductal-postductal SpO2 gradient is significant in the first 20 minutes of life in preterm infants. So, it can be concluded that there is a preductal-postductal SpO2 gradient in preterm infants in the first 20 minutes of life which gradually decreases from 1 to 20 minutes.